A preliminary investigation of polyaniline /chitosan composite's physicochemical properties and potential electrochemical application / Nur Farahin Suhaimi ... [et al.] - Suhaimi, Nur Farahin; Baharin, Siti Nor Atika; Jamion, Nurul Ain; Sambasevam, Kavirajaa Pandian (UiTM Cawangan Negeri Sembilan, 2022)
A polyaniline/chitosan (PANI/CHT) modified SPCE based sensor was developed and validated by electrochemical detection of PFOA. The PANI/CHT composite was synthesized by chemical oxidative polymerization technique. The synthesized material was characterized by scanning electron microscope (SEM)-Energy dispersive X-ray spectroscopy (EDX), Thermal gravimetric analysis (TGA) and Ultraviolet visible Spectroscopy (UV-Vis) techniques. Therefore, from the SEM result showed that the combination of both materials give porous morphology which would further enhance the electrochemical activity of PANI-CHT composite against PFOA. From the TGA analysis also revealed that the addition of CHT to the PANI would increase the thermal stability of the composite compared to the PANI. In addition, the redox properties of the modified SPCE were examined by cyclic voltammetry studies. The investigation showed that PANI/CHT SPCE exhibit high electroactive surface area compared to unmodified SPCE. The PANI/CHT SPCE recorded lowest detection limit (LOD) of 1.60 ppb with LOQ of 4.82 ppb, in the linear range of 25-50 ppb.